Thermoplastic resin composites, thermoplastic resin composite particles and moldings
Patent Information
- Application Number
- JP2022531841
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-15
- Filing Date
- 2021-06-15
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2041-06-15
AI Technical Summary
【0011】 本発明によれば、セルロース繊維を含み、強度等の機械的特性に優れた成形物を得ることができ、溶融時の流動性に優れることで成形加工性に優れた熱可塑性樹脂複合材及び熱可塑性樹脂複合材粒子を提供することができる。
Smart Images

Figure 0007617597000005 
Figure 0007617597000006 
Figure 0007617597000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic resin composite, a thermoplastic resin composite particle, and a molding. [Background technology]
[0002] Thermoplastic resins can be easily molded by heating, and therefore are used as components of various products. From the viewpoints of mass production and manufacturing costs, molding methods using molds, such as injection molding, are generally used for thermoplastic resins.
[0003] In recent years, as electronic devices and the like have become smaller and thinner, the parts used therein have also become smaller and thinner, and thermoplastic resins are required to be moldable into fine and complex shapes. In addition, when thermoplastic resins are used for smaller and thinner parts, they are required to have higher mechanical properties such as strength, and are therefore used in combination with fibers.
[0004] Furthermore, when inorganic fibers are used as fibers to be composited with thermoplastic resins, residues derived from the inorganic fibers are generated during incineration for disposal, and these residues must be disposed of in landfills, etc. For this reason, there is a demand for resin molded products that do not use inorganic fibers, and cellulose fibers are used.
[0005] As a method for producing such a composite resin, for example, Patent Document 1 discloses a method for producing a thermoplastic resin composition containing cellulose fiber, which includes the steps of placing a cellulose fiber aggregate in a mixer having a rotating blade as a stirring means and stirring at high speed to defibrate the cellulose fiber aggregate, placing a thermoplastic resin in the mixer and stirring it to generate frictional heat to melt the thermoplastic resin and obtain a mixture in which the thermoplastic resin adheres to the defibrated cellulose fibers, and stirring the mixture at low speed while cooling. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2007-84713 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, no consideration has been given to the fluidity of the resin composite material during molding of the cellulose fiber-containing thermoplastic resin composition obtained by the manufacturing method of Patent Document 1, and there is a risk that sufficient fluidity will not be obtained during injection molding, etc., resulting in molding defects or insufficient strength of the molded product.
[0008] Therefore, the present invention provides a thermoplastic resin composite or thermoplastic resin composite particles that contain cellulose fibers, can be used to obtain molded products with excellent mechanical properties such as strength, and have excellent fluidity when melted, resulting in excellent moldability. [Means for solving the problem]
[0009] The present inventors have conducted intensive research and found that a thermoplastic resin composite having specific fibers and density (distribution), and a thermoplastic resin composite particle in which specific fibers are oriented in the axial direction and the mass flow rate is adjusted, can solve the above problems, and have completed the present invention. That is, the present invention is as follows.
[0010] The present invention (1) is A thermoplastic resin composite comprising cellulose fibers, a compatibilizer, and a thermoplastic resin, The cellulose fibers substantially contain only fibers having a fiber diameter of 1 to 50 μm and a fiber length of 10 to 400 μm, The composition ratio by mass of the cellulose fiber and the thermoplastic resin is 10:90 to 80:20, The thermoplastic resin composite is characterized in that the standard deviation of the area ratio occupied by the cellulose fibers per specified area in any 10 cross-sections of the thermoplastic resin composite is 15% or less. The present invention (2) is The cellulose fiber is the thermoplastic resin composite of invention (1), characterized in that the fiber bending angle between the axial direction (A) of the fiber at one end and the axial direction (B) of the fiber at the other end is 0 to 60°. The present invention (3) is The thermoplastic resin composite is the thermoplastic resin composite of invention (1) or (2), characterized in that the composition ratio by mass of the cellulose fibers and the thermoplastic resin is 60:40 to 20:80. The present invention (4) is The thermoplastic resin composite according to any one of the above inventions (1) to (3), characterized in that the thermoplastic resin contains any one of polyethylene resin, polypropylene resin, polyvinyl chloride resin, methacrylic resin, polystyrene resin, ABS resin, polycarbonate resin, polyacetal resin, polyamide resin, polysulfone resin, modified PPO resin, and polyester resin. The present invention (5) is A thermoplastic resin composite particle comprising a cellulose fiber and a thermoplastic resin, The average fiber length of the cellulose fibers is 10 to 400 μm, The cellulose fibers have an average fiber diameter of 1 to 50 μm, The content of the cellulose fibers is 20 to 80% by mass, where the sum of the mass of the thermoplastic resin and the mass of the cellulose fibers is 100% by mass. The cellulose fibers are characterized in that they are substantially oriented in the axial direction of the thermoplastic resin composite particle. The present invention (6) is The thermoplastic resin composite particles are the thermoplastic resin composite particles of invention (5), characterized in that the melt mass flow rate measured at 230°C under a load of 2.16 kgf is 5 to 30 (g / 10 min). The present invention (7) is The cellulose fibers are thermoplastic resin composite particles according to invention (5) or (6), characterized in that the fiber bending angle between the fiber axial direction (A) at one end and the fiber axial direction (B) at the other end is 0 to 60°. The present invention (8) is The thermoplastic resin composite particle according to any one of the above inventions (5) to (7), characterized in that the thermoplastic resin contains any one of polyethylene resin, polypropylene resin, vinyl chloride resin, methacrylic resin, polystyrene resin, ABS resin, polycarbonate resin, polyacetal resin, polyamide resin, polysulfone resin, modified PPO resin, and polyester resin. The present invention (9) is The molded product is characterized by being obtained by molding the thermoplastic resin composite particles according to any one of the above inventions (5) to (8). Effect of the Invention
[0011] According to the present invention, it is possible to obtain a molded product containing cellulose fibers and having excellent mechanical properties such as strength, and it is also possible to provide a thermoplastic resin composite and a thermoplastic resin composite particle that have excellent molding processability due to their excellent fluidity when melted. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is an explanatory diagram illustrating an unbent cellulose fiber. [Diagram 2] FIG. 2 is an explanatory diagram illustrating cellulose fibers having a bending angle (bending). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In this application, the term "thermoplastic resin composite" is not limited to particulate materials such as pellets, but also includes processed "thermoplastic resin composites" such as molded products.
[0014] The thermoplastic resin composite and thermoplastic resin composite particles of the present invention will be described below.
[0015] 1. Structure of thermoplastic resin composites and thermoplastic resin composite particles The structure of the thermoplastic resin composite and the thermoplastic resin composite particles is described below.
[0016] 1-1. Structure of thermoplastic resin composite materials The thermoplastic composite of the present invention comprises cellulose fibers and a compatibilizer.
[0017] The composition ratio by mass of the cellulose fibers and the thermoplastic resin is from 10:90 to 80:20, and preferably from 20:80 to 40:60.
[0018] The thermoplastic resin composite has a standard deviation of the area ratio occupied by cellulose fibers per unit area in any 10 cross sections of the thermoplastic resin composite (hereinafter, may be simply referred to as the standard deviation of the area ratio occupied by cellulose fibers) of 15% or less, preferably 13% or less. When the standard deviation of the area ratio occupied by cellulose fibers is within this range, it is possible to obtain a thermoplastic resin composite that has excellent fluidity when melted, and therefore has excellent moldability, and is capable of producing a molded product with excellent mechanical properties such as strength and elastic modulus.
[0019] The standard deviation of the area ratio occupied by cellulose fibers is measured by the following method. A thermoplastic resin composite is cut to form a cross section, and the cross section is observed vertically from above the cross section using a scanning electron microscope at a magnification of 250 times, and an image is taken. Next, the area occupied by cellulose fibers, as observed vertically from above, within a specified area on the cross section surface of the thermoplastic resin composite in the image taken is measured using commercially available software. Here, the specified area on the cross section surface of the thermoplastic resin composite is 2.0 x 10 5 μm 2The occupied area of the cellulose fibers is divided by a specified area on the cross-sectional surface of the thermoplastic resin composite, and the result is multiplied by 100 to obtain the occupied area ratio of the cellulose fibers in the cross-section of the thermoplastic resin composite (hereinafter, this may be simply referred to as the occupied area ratio of the cellulose fibers). The same measurement is performed on 10 arbitrary cross-sections of the thermoplastic resin composite, and the standard deviation of the obtained occupied area ratios of the five cellulose fibers is calculated to obtain the standard deviation of the occupied area ratio of the cellulose fibers.
[0020] The standard deviation of the area ratio occupied by the cellulose fibers can be adjusted by changing the rotation speed and screw pattern of the kneading means when kneading the cellulose fibers and the thermoplastic resin, which will be described later.
[0021] The shape and size of the thermoplastic resin composite of the present invention are not particularly limited, but for example, when used in injection molding or the like, pellet-like particles are preferred, and the size may be a sphere, elliptical sphere, cylinder, polygonal column, cone, polygonal pyramid, etc., with a diameter, major axis length, or maximum side length of about 0.5 to 10 mm. In the present invention, molded products obtained by molding or the like using these thermoplastic resin composites are also included in the thermoplastic resin composite, and in that case, the shape may be any desired shape.
[0022] The composition ratio by mass of the cellulose fibers and the thermoplastic resin is 10:90 to 80:20, and preferably 20:80 to 60:40. When it is within this range, it is possible to obtain a thermoplastic resin composite material that has excellent flowability when melted, and therefore has excellent moldability, and that can give a molded product having excellent mechanical properties such as strength and elastic modulus.
[0023] The cellulose fibers contained in the thermoplastic resin composite of the present embodiment preferably contain substantially only fibers having a fiber diameter of 1 to 50 μm. When the fiber diameter is within the above range, a thermoplastic resin composite can be obtained that has excellent flowability when melted, and therefore has excellent moldability, and is capable of producing a molded product having excellent mechanical properties such as strength and elastic modulus.
[0024] In a thermoplastic resin composite, the cellulose fibers essentially contain only fibers having a fiber diameter of 1 to 50 μm means that when the fiber diameter of the cellulose fibers in the thermoplastic resin composite is measured by the following method, no cellulose fibers other than those having a fiber diameter of 1 to 50 μm are detected. In other words, the cellulose fibers preferably contain only fibers having a fiber diameter of 1 to 50 μm. The cellulose fibers containing only fibers having a fiber diameter of 1 to 50 μm means that when the thermoplastic resin composite of the present invention is photographed using an X-ray CT analyzer and the fiber diameters of all the cellulose fibers are measured, the cellulose fibers (fiber diameters of all the cellulose fibers) are all fibers having a fiber diameter of 1 to 50 μm. The fiber diameter of the cellulose fiber is measured by photographing the thermoplastic resin composite using an X-ray CT analyzer and measuring the fiber diameter of all fibers (the long axis length in the case of an ellipse, and the longest side length in the case of a polygon). The X-ray CT analyzer is used under the following observation conditions. Analyzer: Rigaku high resolution 3DX ray microscope nano3DX Measurement conditions: X-ray source Cu (40kV, 30mA) Analysis software: Dragonfly Object Research Systems Image size: 347.7 x 763.2 μm Thickness: 654 μm
[0025] The fiber diameter of the cellulose fibers can be adjusted by changing the load due to the rotation speed and screw pattern of the kneading means when kneading the cellulose fibers and the thermoplastic resin described below, or by changing the compounding ratio of the cellulose fibers.
[0026] The cellulose fibers contained in the thermoplastic resin composite of the present invention preferably contain substantially only fibers having a fiber length of 10 to 400 μm, and more preferably contain substantially only fibers having a fiber length of 10 to 350 μm. When the fiber length is within the above range, a thermoplastic resin composite can be obtained that has excellent flowability when melted, and therefore excellent moldability, and that can give molded products having excellent mechanical properties such as strength and elastic modulus.
[0027] In a thermoplastic resin composite, the cellulose fibers essentially contain only fibers having a fiber length of 10 to 400 μm (fibers having a fiber length of 10 to 350 μm) means that when the fiber length of the cellulose fibers in the thermoplastic resin composite is measured by the following method, no cellulose fibers other than cellulose fibers having a fiber length of 10 to 400 μm (10 to 350 μm) are detected. In other words, the cellulose fibers preferably contain only fibers having a fiber length of 10 to 400 μm (10 to 350 μm). The term "cellulose fibers containing only fibers having a fiber length of 10 to 400 μm (10 to 350 μm)" means that when the thermoplastic resin composite of the present invention is photographed using an X-ray CT analyzer and the fiber lengths of all the cellulose fibers are measured, the cellulose fibers (the fiber lengths of all the cellulose fibers) are all fibers having a fiber length of 10 to 400 μm (10 to 350 μm). The fiber length of the cellulose fibers is measured by photographing the thermoplastic resin composite using an X-ray CT analyzer and measuring the fiber lengths of all the fibers. The X-ray CT analyzer is used under the following observation conditions. Analyzer: Rigaku high resolution 3DX ray microscope nano3DX Measurement conditions: X-ray source Cu (40kV, 30mA) Analysis software: Dragonfly Object Research Systems (Canada) Image size: 347.7 x 763.2 μm Thickness: 654 μm
[0028] The fiber length of the cellulose fibers can be adjusted by changing the load due to the rotation speed and screw pattern of the kneading means when kneading the cellulose fibers and the thermoplastic resin described below, or by changing the compounding ratio of the cellulose fibers.
[0029] The bending angle of the cellulose fibers, which is the angle between the axial direction of the fibers at one end and the axial direction of the fibers at the other end, can be 0 to 60°, preferably 0 to 50°, and more preferably 0 to 40°. When the bending angle of the cellulose fibers is within the above range, the cellulose fibers are less entangled with each other, and the thermoplastic resin composite can be obtained, which has excellent fluidity when melted, excellent moldability, and is capable of producing a molded product having excellent mechanical properties such as strength and elastic modulus.
[0030] The bending angle of cellulose fibers will be described below with reference to Figs. 1 and 2. Fig. 1 is a perspective view (Fig. 1(a)) showing cellulose fibers when not bent (bending angle is 0°) and a top view (Fig. 1(b)) showing the cellulose fibers. The cellulose fibers 1 have one end 10 and the other end 12. The one end 10 and the other end 12 can be arbitrarily determined. The axial direction 11 at the one end 10 is defined as the axial direction (A). The axial direction 13 at the other end 12 is defined as the axial direction (B). The axial direction (A) is defined as a positive direction from the one end 10 toward the fiber side (the direction of the arrow in the figure) with respect to the one end, and is defined as 0°. The axial direction (B) is defined as a positive direction from the fiber side toward the other end (the direction of the arrow in the figure) with respect to the other end, and is defined as 0°. 1(a) and (b), axial direction 11 (axial direction (A)) and axial direction 13 (axial direction (B)) are in the same direction and overlap each other. That is, the bending angle is 0° and the fibers are straight.
[0031] FIG. 2 is a perspective view (FIG. 2(a)) and a top view (FIG. 2(b)) of cellulose fibers in a bent state, i.e., when the fibers have a bend angle. As in the case of FIG. 1, the cellulose fibers 2 have one end 20 and the other end 22. The one end 20 and the other end 22 can be determined arbitrarily. The axial direction 21 at the one end 20 is defined as the axial direction (A). The axial direction 23 at the other end 22 is defined as the axial direction (B). The top view of FIG. 2(b) is a top view observed from the normal direction of a plane including the axial directions 21 and 23. The axial direction (A) is defined as a positive direction from the one end 20 toward the fiber side (the direction of the arrow in the figure) with respect to the one end as a reference, and is defined as 0°. The axial direction (B) is defined as a positive direction from the fiber side toward the other end (the direction of the arrow in the figure) with respect to the other end as a reference, and is defined as 0°. 2(a) and (b), the angle (α in the figure) between axial direction 21 (axial direction (A)) and axial direction 23 (axial direction (B)) and their respective positive axial directions is defined as the bending angle.
[0032] The bending angle of the cellulose fibers can be adjusted by adjusting the balance between the fiber diameter and the fiber length of the cellulose fibers.
[0033] 1-2. Structure of thermoplastic resin composite particles The thermoplastic resin composite particles of the present invention include cellulose fibers and a thermoplastic resin.
[0034] The thermoplastic resin composite particles are columnar particles. Here, columnar is not limited to a circular cylinder, an elliptical cylinder, or a polygonal cylinder, but includes shapes that are generally considered to be columnar.
[0035] The shape of the thermoplastic resin composite particles is preferably 0.5 to 10 mm in diameter, major axis length or maximum side length. The shape of the thermoplastic resin composite particles can be observed and measured, for example, using a scale or an optical microscope.
[0036] The thermoplastic resin composite particles are characterized in that the melt mass flow rate (hereinafter sometimes abbreviated as MRF) measured at 230° C. and a load of 2.16 kgf is 5 to 30 g / 10 min. The melt mass flow rate particularly affects molding processability, and a larger melt mass flow rate is preferable because it improves molding processability, and the upper limit is 30 g / 10 min, depending on the combination of the melt mass flow rate of a typical thermoplastic resin alone and the range of the composition ratio of the cellulose fiber and the thermoplastic resin.
[0037] The melt mass flow rate is measured using the method described in JIS K7210-1:2014 "Plastics - Determination of melt mass flow rate (MFR) and melt volume flow rate (MVR) of thermoplastics - Part 1: Standard test method". The measurement conditions are 230°C and a load of 2.16 kgf.
[0038] The content of the cellulose fibers is 20 to 80% by mass, preferably 40 to 70% by mass, when the sum of the mass of the thermoplastic resin and the mass of the cellulose fibers is taken as 100% by mass. When the content is within this range, it is possible to increase the orientation of the cellulose fibers, and it is possible to obtain thermoplastic resin composite particles that have excellent flowability when melted, and therefore excellent moldability, and that can give molded products with excellent mechanical properties such as strength and elastic modulus.
[0039] When the total mass of the thermoplastic resin composite particles is taken as 100 mass%, the sum of the mass of the thermoplastic resin and the mass of the cellulose fiber is 90 to 99.9 mass%, preferably 95 to 99.5 mass%, and more preferably 97 to 99 mass%. When it is within such a range, it is possible to obtain thermoplastic resin composite particles that have excellent flowability when melted, and therefore have excellent moldability, and can give molded products with excellent mechanical properties such as strength and elastic modulus. The average fiber length of the cellulose fibers is 10 to 400 μm, and preferably 10 to 350 μm. When the average fiber length is within the above range, it is possible to obtain thermoplastic resin composite particles that have excellent flowability when melted, and therefore excellent moldability, and that can give molded products having excellent mechanical properties such as strength and elastic modulus.
[0040] The average fiber length of the cellulose fibers is obtained by randomly selecting 50 cellulose fibers contained in the thermoplastic resin composite particles of the present invention, photographing them using a scanning electron microscope, measuring the fiber lengths of the cellulose fibers, and calculating the number average.
[0041] The average fiber length of the cellulose fibers can be adjusted by changing the load due to the rotation speed and screw pattern of the kneading means when kneading the cellulose fibers and the thermoplastic resin described below, or by changing the compounding ratio of the cellulose fibers.
[0042] The average fiber diameter of the cellulose fibers is 1 to 50 μm. When the average fiber diameter is within this range, it is possible to obtain thermoplastic resin composite particles that have excellent flowability when melted, and therefore excellent moldability, and that can give molded products with excellent mechanical properties such as strength and elastic modulus.
[0043] The average fiber diameter of the cellulose fibers is obtained by randomly selecting 50 cellulose fibers contained in the thermoplastic resin composite particles of the present invention, photographing them using a scanning electron microscope, measuring the diameters of the cellulose fibers (the long axis length in the case of an ellipse, and the longest side length in the case of a polygon), and calculating the number average thereof.
[0044] The average fiber diameter of the cellulose fibers can be adjusted by changing the load due to the rotation speed and screw pattern of the kneading means when kneading the cellulose fibers and the thermoplastic resin described below, or by changing the compounding ratio of the cellulose fibers.
[0045] It is preferable that the cellulose fibers are substantially oriented in the axial direction of the thermoplastic resin composite particles. In the present invention, the cellulose fibers are substantially oriented in the axial direction of the thermoplastic resin composite particles when the angle (hereinafter sometimes referred to as the orientation angle) between the axial direction (x) of the longest straight portion of the cellulose fibers and the axial direction (y) of the thermoplastic resin composite particles is within ±30° (or ±150°). Here, the orientation angle is the smaller angle between the axial direction (x) of the longest straight portion of the cellulose fibers and the axial direction (y) of the thermoplastic resin composite particles. More specifically, the orientation of the cellulose fibers in the axial direction of the thermoplastic resin composite particles is determined as follows. Among the cellulose fibers contained in the cross section in the axial direction of the thermoplastic resin composite particle (any cross section in which the axial direction of the thermoplastic resin composite particle and the normal direction of the cross section are perpendicular to each other), 50 fibers having a fiber length of 50 to 400 μm are randomly selected, and the orientation angle between the axial direction of the thermoplastic resin composite particle and the axial direction of the longest straight part of the selected 50 cellulose fibers is measured. The ratio of the cellulose fibers whose orientation angles are within ±30° is 80% or more (i.e., 40 or more) of the selected 50 cellulose fibers, and the fibers are considered to be oriented. The ratio of the cellulose fibers whose orientation angles are within ±30° is preferably 85% or more, more preferably 90% or more, of the selected 50 cellulose fibers. In this way, if the proportion of such cellulose fibers with an orientation angle within ±30° is high among the 50 selected cellulose fibers, entanglement of the cellulose fibers is suppressed, and therefore it is possible to obtain thermoplastic resin composite particles that have excellent fluidity when melted, excellent moldability, and can produce molded products with excellent mechanical properties such as strength and elastic modulus. The fiber length and orientation angle of these cellulose fibers are measured by observation using an X-ray CT analyzer.
[0046] The orientation of the cellulose fibers in the axial direction of the thermoplastic resin composite particles can be adjusted by changing the cellulose fiber length or the method of strand cutting during granulation, which will be described later.
[0047] The bending angle of the cellulose fibers, which is the angle between the axial direction of the fibers at one end and the axial direction at the other end, can be 0 to 60°, preferably 0 to 50°, and more preferably 0 to 40°. When the bending angle of the cellulose fibers is within the above range, the cellulose fibers are less entangled with each other, and the thermoplastic resin composite particles can be obtained, which have excellent fluidity when melted, excellent moldability, and therefore excellent mechanical properties such as strength and elastic modulus.
[0048] The bending angle of cellulose fibers will be described below with reference to Figs. 1 and 2. Fig. 1 is a perspective view (Fig. 1(a)) showing cellulose fibers when not bent (bending angle is 0°) and a top view (Fig. 1(b)) showing the cellulose fibers. The cellulose fibers 1 have one end 10 and the other end 12. The one end 10 and the other end 12 can be arbitrarily determined. The axial direction 11 at the one end 10 is defined as the axial direction (A). The axial direction 13 at the other end 12 is defined as the axial direction (B). The axial direction (A) is defined as a positive direction from the one end 10 toward the fiber side (the direction of the arrow in the figure) with respect to the one end, and is defined as 0°. The axial direction (B) is defined as a positive direction from the fiber side toward the other end (the direction of the arrow in the figure) with respect to the other end, and is defined as 0°. 1(a) and (b), axial direction 11 (axial direction (A)) and axial direction 13 (axial direction (B)) are in the same direction and overlap each other. That is, the bending angle is 0° and the fibers are straight.
[0049] FIG. 2 is a perspective view (FIG. 2(a)) and a top view (FIG. 2(b)) of cellulose fibers in a bent state, i.e., when the fibers have a bend angle. As in the case of FIG. 1, the cellulose fibers 2 have one end 20 and the other end 22. The one end 20 and the other end 22 can be determined arbitrarily. The axial direction 21 at the one end 20 is defined as the axial direction (A). The axial direction 23 at the other end 22 is defined as the axial direction (B). The top view of FIG. 2(b) is a top view observed from the normal direction of a plane including the axial directions 21 and 23. The axial direction (A) is defined as a positive direction from the one end 20 toward the fiber side (the direction of the arrow in the figure) with respect to the one end as a reference, and is defined as 0°. The axial direction (B) is defined as a positive direction from the fiber side toward the other end (the direction of the arrow in the figure) with respect to the other end as a reference, and is defined as 0°. 2(a) and (b), the angle (α in the figure) between axial direction 21 (axial direction (A)) and axial direction 23 (axial direction (B)) and their respective positive axial directions is defined as the bending angle.
[0050] The bending angle of the cellulose fibers can be adjusted by adjusting the balance between the fiber diameter and the fiber length of the cellulose fibers.
[0051] 2.Raw materials for thermoplastic resin composites and thermoplastic resin composite particles The raw materials for the thermoplastic resin composite and thermoplastic resin composite particles of the present invention will be described below.
[0052] 2-1.Thermoplastic resin The thermoplastic resin composite and thermoplastic resin composite particles of the present invention have a thermoplastic resin as a binder layer. The thermoplastic resin is not particularly limited as long as it does not impair the effects of the invention, and examples thereof include polyethylene resin, polypropylene resin, vinyl chloride resin, methacrylic resin, polystyrene resin, ABS resin, polycarbonate resin, polyacetal resin, polyamide resin, polysulfone resin, modified PPO resin, and polyester resin. These can be used alone or in combination. From the viewpoint of being able to obtain a thermoplastic resin composite and a thermoplastic resin composite particle that can obtain a molded product having excellent mechanical properties such as strength and elastic modulus due to excellent fluidity when melted, and excellent moldability, polyethylene resin and polypropylene resin are preferred, and polypropylene resin is more preferred from the viewpoint of being able to obtain a thermoplastic resin composite and a thermoplastic resin composite particle that can obtain a molded product having excellent mechanical properties such as strength and elastic modulus.
[0053] 2-2. Cellulose fiber The cellulose fiber according to the present invention is not particularly limited as long as it does not impair the effects of the present invention. That is, in a suitable method for producing the thermoplastic resin composite and thermoplastic resin composite particles of the present invention, which are obtained by defibrating pulp, described later, the pulp is pulverized (defibrated) to form cellulose fibers, so cellulose fibers derived from pulp are preferred. Pulp is defibrated into cellulose fibers, but the thermoplastic resin composite and thermoplastic resin composite particles of the present invention may contain an aggregate of multiple cellulose fibers after defibration.
[0054] The pulp according to the present invention is not particularly limited as long as it does not impair the effects of the present invention. From the viewpoint of the raw material, it may be either wood pulp or non-wood pulp, and from the viewpoint of the production method, it may be either mechanical pulp or chemical pulp.
[0055] Examples of wood pulp include MP, CP, GP, RGP, CGP, SP, AP, KP, SCP, etc. made from conifers such as fir and pine, and broad-leaved trees such as eucalyptus and poplar, and these may be unbleached or bleached pulp.
[0056] Non-wood pulp includes natural fibers other than wood, such as cotton, straw, bamboo, esparto, bagasse, linter, kenaf, hemp pulps such as Manila hemp, flax, hemp, and jute, and gampi pulp, as well as waste paper pulp made from waste paper and scraps.
[0057] Pulp can be used alone or in combination. Among these, pulp from coniferous trees, broadleaf trees, cotton, and hemp are preferred, and pulp from coniferous trees and broadleaf trees is more preferred. These pulps have excellent fluidity when melted, and therefore have excellent moldability, and can provide thermoplastic resin composites and thermoplastic resin composite particles that can provide molded products with excellent mechanical properties such as strength and elastic modulus. Pulp from coniferous trees is preferred because it contains less lignin, hemicellulose, etc., which are sources of odor and color, and the removal process of these substances is relatively easy, making the manufacturing process simple.
[0058] 2-3. Compatibilizer The thermoplastic resin composite of the present invention includes a compatibilizer. The thermoplastic resin composite particles of the present invention may also include a compatibilizer.
[0059] The compatibilizer is not particularly limited as long as it does not impair the effects of the present invention, and can be selected depending on the combination of cellulose fiber and thermoplastic resin. The compatibilizer is used to disperse the relatively hydrophilic cellulose fiber in the relatively hydrophobic thermosetting resin. Therefore, the compatibilizer is preferably a block copolymer having a non-polar segment and a polar segment. Here, the non-polar segment is preferably an olefin-based segment. In addition, the thermoplastic resin composite particle of the present invention can obtain the effects of the present invention even if it does not contain a compatibilizer, but when it contains a compatibilizer, the dispersibility of the cellulose fiber is better, so that the entanglement of the cellulose fibers is reduced and the cellulose fibers are easily oriented in the axial direction of the thermoplastic resin composite particle. For this reason, it is possible to obtain a thermoplastic resin composite particle that is excellent in moldability due to its excellent fluidity when melted, and that can obtain a molded product with excellent mechanical properties such as strength and elastic modulus. Furthermore, when the cellulose fiber and the thermoplastic resin are kneaded, the cellulose fiber is easily dispersed in the thermoplastic resin, making it easy to manufacture.
[0060] Here, the olefin-based segment is a segment in which an olefin-based monomer is polymerized or an olefin-based monomer and a styrene-based monomer are copolymerized. Examples of the olefin-based monomer include ethylene, propylene, methylpentene, butadiene, and norbornene derivatives. Only one type of olefin-based monomer may be used, or two or more types may be used.
[0061] The polar segment is preferably an ester-based segment or a styrene-based segment.
[0062] The ester-based segment is a segment formed by condensation polymerization of an alcohol-based monomer and an acid-based monomer.
[0063] Examples of alcohol monomers include α,ω-alkylenediols (C2 to C12) such as ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol; polyalkylene glycols such as diethylene glycol, triethylene glycol, and dipropylene glycol; aliphatic dihydric alcohols such as 1,2-propanediol, neopentyl glycol, and 1,4-cyclohexanedimethanol; and sugars such as glycerin, 1,1,1-tris(4-hydroxyphenyl)ethane, trimethylolethane, trimethylolpropane, monosaccharides, disaccharides, ring-opened sugars, and modified sugars. Examples of the bisphenols that can be used include polyhydric alcohols such as those listed above, 2,2-bis(4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(3-phenyl-4-hydroxyphenyl)propane, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl ether, and bis(4-hydroxyphenyl)diphenylmethane, as well as bisphenols whose hydroxyl groups have been modified with alkylene glycols such as polyethylene glycol and polypropylene glycol, and bisphenols whose aromatic rings have been hydrogenated.
[0064] Examples of the acid monomer include saturated aliphatic carboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and octyl succinic acid; unsaturated aliphatic carboxylic acids such as maleic acid, fumaric acid, and maleic anhydride; cyclic aliphatic carboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and 2,3-bicyclo[2,2,1]dicarboxylic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and naphthalene dicarboxylic acid; and polyvalent carboxylic acids having a valence of three or more such as trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic anhydride, 1,2,4-cyclohexanetricarboxylic acid, 1,2,4-cyclohexanetricarboxylic acid anhydride, 1,2,4-butanetricarboxylic acid, 1,2,4-butanetricarboxylic acid anhydride, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, and 1,2,4-naphthalenetricarboxylic acid anhydride. The carboxylic acid may be an acid halide, an ester, or an acid anhydride. Among these, maleic anhydride-modified polypropylene, which has been successfully modified while maintaining a high molecular weight, has improved adhesion to fillers and entangles at the molecular level, thereby enabling the strength of polyolefin composite materials to be enhanced.
[0065] The styrene-based segment is a segment in which a styrene-based monomer is polymerized or a styrene-based monomer is copolymerized with an acrylic monomer. Examples of the styrene-based monomer include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, p-methoxystyrene, p-phenylstyrene, p-chlorostyrene, and 3,4-dichlorostyrene. Examples of acrylic monomers include n-butyl methacrylate, isobutyl methacrylate, ethyl acrylate, n-butyl acrylate, methyl methacrylate, glycidyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, diethylaminopropyl acrylate, 2-ethylhexyl acrylate, butyl acrylate-N-(ethoxymethyl)acrylamide, ethylene glycol methacrylate, and 4-hexafluorobutyl methacrylate. These acrylic monomers can be used alone or in combination. These monomers may be modified.
[0066] In addition, the compatibilizer may contain other monomers polymerized therein, so long as they do not impair the effects of the present invention. Examples of the other monomers include vinyl monomers, such as vinyl ester monomers such as vinyl acetate, vinyl propionate, vinyl benzoate, and vinyl butyrate, vinyl ether monomers such as vinyl methyl ether, vinyl ethyl ether, and vinyl butyl ether, vinyl ketone monomers such as vinyl methyl ketone, vinyl hexyl ketone, and vinyl isopropenyl ketone, and diene monomers such as isoprene and 2-chlorobutadiene.
[0067] The content of the compatibilizer is not particularly limited as long as the effects of the present invention are not inhibited, and for example, when the total mass of the thermoplastic resin composite and the thermoplastic resin composite particles is taken as 100 mass%, it can be 0.1 to 10 mass%, preferably 0.5 to 5 mass%, and more preferably 1 to 3 mass%. When the content of the compatibilizer is within this range, it is possible to obtain a thermoplastic resin composite and a thermoplastic resin composite particle that have excellent flowability when melted, and therefore excellent moldability, and that can produce a molded product having excellent mechanical properties such as strength and elastic modulus.
[0068] 3. Method for producing thermoplastic resin composite and thermoplastic resin composite particles A preferred embodiment of the method for producing the thermoplastic resin composite and thermoplastic resin composite particles of the present invention will be described below. The method for producing the thermoplastic resin composite and thermoplastic resin composite particles of the present invention is not limited thereto. The pulp is kneaded and then defibrated into cellulose fibers. Therefore, the amount of cellulose fibers added is equal to the amount of pulp added.
[0069] 3-1. Coarse grinding process The pulp is crushed into small pieces of pulp in a coarse crushing process before being mixed with the thermoplastic resin. The size of the small pulp pieces is not particularly limited, but for ease of mixing and shortening the time of the kneading process, it is preferable that the diameter or longest side of the small pulp pieces is 10 to 50 mm. By making the size of the small pulp pieces, excellent dispersibility is exhibited in the kneading process.
[0070] The coarse pulverization can be carried out by using a known method, for example, a pulverization method using a pulverizer such as a hammer mill, a cutter mill, or a jet mill.
[0071] 3-2.Kneading process The thermoplastic resin, pulp pieces, and compatibilizer are mixed and then kneaded. The mixing method and kneading method are not particularly limited and can be performed by a known method. In the kneading step, the pulp pieces are pulverized (defibrated) into cellulose fibers, and the cellulose fibers are kneaded with the thermoplastic resin.
[0072] The mixing method may be a method using a mixer such as a Henschel mixer, a super mixer, or a ribbon mixer.
[0073] Examples of the kneading method include a method using a twin-screw extruder, a method using a Banbury mixer, a method using a pressure roller, and the like.
[0074] The kneading is generally performed by heating, and although the kneading conditions are not particularly limited, it is preferable to set the heating temperature to the softening point of the thermoplastic resin or higher. By setting the temperature at such a temperature, it is possible to obtain a thermoplastic resin composite and a thermoplastic resin composite particle that have excellent flowability when melted, excellent moldability, and can obtain a molded product with excellent mechanical properties such as strength and elastic modulus. This allows the resin and cellulose fibers to be kneaded, and a thermoplastic resin composite and a thermoplastic resin composite particle that are uniformly dispersed without fiber agglomerates can be obtained.
[0075] 3-3. Granulation process The kneaded product obtained in the kneading step is made into a particulate (eg, pellet-shaped) thermoplastic resin composite or thermoplastic resin composite particles in a granulation step.
[0076] The granulation method is to extrude the kneaded resin from a die of an extruder and cut it into pellets with a rotary knife under air cooling. The cut length of the pellets can be changed by adjusting the rotation speed of the rotary knife. The particle shape is not particularly limited, and can be, for example, a polygonal column or a cylindrical shape.
[0077] 3-4. Applications of thermoplastic resin composites and thermoplastic resin composite particles The thermoplastic resin composite and thermoplastic resin composite particles of the present invention can be used as raw materials for molded products in a molding method using a mold such as injection molding, a molding method using a 3D printer, etc. In particular, they are suitable for use in molded parts for vehicles, equipment, devices, etc. having fine structures or complex structures, industrial materials such as containers, pallets, plastic cores, building materials, daily necessities, and miscellaneous goods. EXAMPLES
[0078] <<Examples 1 to 8 and Comparative Examples 1 to 4>> <Preparation of thermoplastic resin composite material> (raw materials) ·Thermoplastic resin Polypropylene (Novatec MG03BD) Polyethylene (Japan Polyethylene UJ480) Pulp (raw material for cellulose fibers) Softwood pulp (NBKP manufactured by Canfor) Hardwood pulp (Suzano LBKP) Compatibilizer Compatibilizer (KAYABRID 002PP-NW, manufactured by Kayaku Akzo Co., Ltd.)
[0079] (Preparation of Thermoplastic Resin Composites in Each Example and Comparative Example) The pulp was weighed out in the amount shown in Table 1, and coarsely crushed using a crusher until the pulp became small pieces with a length of 40 mm or less and a width of 10 mm or less. The obtained pulp pieces were mixed with the pulp pieces and resin in the mass ratio shown in Table 1. Furthermore, a compatibilizer was added so that the compatibilizer was 1 mass% when the total mass of the mixture of the obtained pulp pieces, thermoplastic resin, and compatibilizer was 100 mass%, and dry blended to obtain the mixture of each Example and Comparative Example. Each of the obtained mixtures was melt-kneaded by the manufacturing methods i to vi shown in Table 2 using a twin-screw kneader (PCM30 manufactured by Ikegai Corporation). The details of the manufacturing methods i to vi are shown in Table 2. The obtained kneaded products of each Example and Comparative Example were hot-cut to obtain pellets of the thermoplastic composite material of each Example and Comparative Example. The dispersibility in Table 2 was evaluated according to the following evaluation criteria. (Evaluation Criteria for Dispersibility) ◎: Standard deviation of area ratio is 13% or less ○: Standard deviation of area ratio is more than 13% and 15% or less △: Standard deviation of area ratio is more than 15% ×: Standard deviation of area ratio could not be measured
[0080] The fiber diameter and fiber length of the cellulose fibers in the obtained pellets of Examples 1 to 8 and Comparative Examples 1 to 4, the standard deviation of the area ratio occupied by the cellulose fibers per given area of any 10 cross sections, and the bending angle were measured by the methods described above. The results are shown in Table 1. In Comparative Examples 1 and 4, the dispersibility of the cellulose fibers was poor (they were present as small pieces of pulp, i.e., they were not defibrated into cellulose fibers and were in an agglomerated state), and it was not possible to measure the fiber diameter and fiber length of the cellulose fibers, the standard deviation of the area ratio occupied by the cellulose fibers per given area of any 10 cross sections, and the bending angle.
[0081] <<Examples 9 to 29 and Comparative Examples 5 to 10>> <Preparation of thermoplastic resin composite particles> (raw materials) ·Thermoplastic resin Polypropylene (Novatec MG03BD) Polyethylene (Japan Polyethylene UJ480) Pulp (raw material for cellulose fibers) Softwood pulp (NBKP manufactured by Canfor) Hardwood pulp (Suzano LBKP) Cotton pulp (manufactured by Toho Tokushu Pulp Co., Ltd.) Hemp pulp (Philippine abaca pulp made by Toho Tokushu Pulp Co., Ltd.) Compatibilizer Compatibilizer (KAYABRID 002PP-NW, manufactured by Kayaku Akzo Co., Ltd.)
[0082] (Preparation of Thermoplastic Resin Composite Particles of Examples 9 to 29 and Comparative Examples 5 to 10) The amount of pulp shown in Tables 3 and 4 was weighed out, and the pulp was roughly pulverized using a pulverizer until the pulp became small pieces with a length of 40 mm or less and a width of 10 mm or less. The obtained small pieces of pulp were mixed with the pulp pieces and resin in the mass ratio shown in Tables 3 and 4. Furthermore, a compatibilizer was added so that the compatibilizer was 1 mass% when the total mass of the mixture of the obtained small pieces of pulp, thermoplastic resin, and compatibilizer was taken as 100 mass%, and the mixture was dry-blended to obtain mixtures of each Example and Comparative Example. Each of the obtained mixtures was kneaded using a twin-screw kneader (PCM30 manufactured by Ikegai Corporation) under conditions of a feed rate of 5 kg / h, a rotation speed of 200 rpm, and a kneading temperature of 120 to 150°C. The obtained kneaded material was cut into cylindrical particles with a length of 6 mm and a width of 3 mm and strand-cut (a method in which the resin is discharged from the extruder in a thin rod shape, immersed in water to cool and cut) under the following conditions A to D (resin extrusion conditions from the extruder during granulation) to obtain thermoplastic resin composite particles for Examples 9 to 29 and Comparative Examples 5 to 10. A: The resin is discharged from the extruder, stretched about 1m in the air, and then immersed in water. B: The resin is discharged from the extruder, immediately immersed in water, and stretched. C: The resin is discharged from the extruder and immediately immersed in water (without stretching). D: The resin is discharged from the extruder. (It is not immersed in water and is not stretched.)
[0083] The average fiber diameter and average fiber length of the cellulose fibers in the thermoplastic resin composite particles of Examples 9 to 29 and Comparative Examples 5 to 10, and 50 cellulose fibers with fiber lengths of 50 to 400 μm were randomly selected from among the cellulose fibers contained in any cross section in which the axial direction of the thermoplastic resin composite particle and the normal direction of the cross section in the axial direction of the thermoplastic resin composite particle are perpendicular to each other, and the ratio of those in which the orientation angle between the axial direction of the thermoplastic resin composite particle and the axial direction of the longest straight part of the selected 50 cellulose fibers is within ±30°, and the bending angle were measured by the above-mentioned method. The results are shown in Tables 3 and 4.
[0084] <<Other measurements>> (Melt Mass Flow Rate) The flow rate of the pellets of each Example and Comparative Example was measured using a measuring device (Melt Indexer F-F01 manufactured by Toyo Seiki Co., Ltd.) at a temperature of 230° C. and a load of 2.16 kgf. The results are shown in Tables 1, 3, and 4.
[0085] (Tensile strength) The pellets of each Example and Comparative Example were dried in a dryer at 80°C for 30 minutes, and the resin was melted using an injection molding machine (Nissei Plastic Industrial Co., Ltd.: TD100-25ASE) under conditions of a cylinder temperature and a nozzle temperature of 180°C, fed into a mold in the shape of a dumbbell-shaped test piece, and cooled to obtain a molded body. The molded body was a dumbbell-shaped test piece, and had the dimensions of a plate-shaped test piece specified in JIS Z2201:1968. The tensile strength of each of the obtained dumbbell-shaped test pieces was measured using an Instron-type material testing machine (Shimadzu Corporation: Autograph AG25 TA) at a crosshead speed of 50 mm / min from the load at the time of breakage. The measurement results are shown in Tables 1, 3, and 4.
[0086] (Bending strength) The pellets of each Example and Comparative Example were used to prepare the same test pieces as those for the tensile strength described above. The resulting dumbbell-shaped test pieces were subjected to bending strength measurement using an Instron-type material testing machine (RTC-2410, A&D Co., Ltd., load cell 5kN) with a support distance of 60 mm, a 5 mm radius indenter was brought into contact with the center of the plane of the test piece, and a load was applied, based on the load at which the test piece broke. The test piece was set so that the load applied by the indenter was parallel to the thickness direction of the test piece, and the bending strength was measured at a crosshead speed of 2 mm / min. The measurement results are shown in Tables 1, 3, and 4.
[0087] (Heavy Deflection Temperature (HDT)) The test pieces of each Example and Comparative Example were prepared in the same manner as the preparation method of the test piece for tensile strength, except that the mold was changed to one for the test piece shape (length 80±2.0 mm x width 10±0.2 mm x thickness 4±0.2 mm) specified in JIS K7191:2007 "Plastics - Determination of deflection temperature under load - Part 1: General rules". The deflection temperature under load was measured using an HDT test device (3M-2 manufactured by Toyo Seiki Seisakusho Co., Ltd.). The measurement conditions were a measurement start temperature of 60°C, a heating rate of 2°C / min, and a bending stress of 0.45 MPa, and the temperature at which the deflection amount reached 0.34 mm was measured as the deflection temperature under load. The results are shown in Tables 1, 3, and 4.
[0088] (Moldability) The pellets of each Example and Comparative Example were injection molded under molding conditions of a temperature of 180°C, an injection force of 800 to 1000 MPa, and a mold temperature of 60°C to prepare dumbbell test pieces having a total length of 174.25 mm, a width of 20.5 mm, and a thickness of 4 mm. (Evaluation Criteria) ◎: Dumbbell test piece can be molded normally ○: Molding can only be completed halfway under the set conditions, but molding can be completed by increasing the pressure to 1500 MPa. △: Even after changing the pressure, molding is only possible halfway, but if the temperature is raised to 200℃, molding is possible. ×: The gate is clogged and molding is not possible.
[0089] [Table 1]
[0090] [Table 2]
[0091] In Table 2, NDW indicates that kneading disk W was used, NDL indicates that kneading disk L was used, and NDR indicates that kneading disk R was used, and NDW means that the kneading strength was relatively strong, NDL means that the kneading strength was relatively medium, and NDR means that the kneading strength was relatively weak. The dispersibility in Table 2 was evaluated by observing the cross section of the pellets produced under each production condition using a scanning electron microscope and using the following evaluation criteria.
[0092] [Table 3]
[0093] [Table 4] In addition, Comparative Example 8 could not be molded, and Comparative Example 9 had poor moldability and could not be evaluated. [Explanation of symbols]
[0094] 1. Unbent cellulose fibres 2. Bent cellulose fibers 10 One end (optional) 11 Axial direction of one end (Axial direction (A)) 12 Other end (optional) 13 Axial direction of the other end (Axial direction (B)) α bending angle
Claims
1. A thermoplastic resin composite comprising cellulose fibers, a compatibilizer, and a thermoplastic resin, The cellulose fibers substantially contain only fibers having a fiber diameter of 1 to 50 μm and a fiber length of 10 to 400 μm, The composition ratio by mass of the cellulose fiber and the thermoplastic resin is 10:90 to 80:20, The thermoplastic resin composite is characterized in that the standard deviation of the area ratio occupied by the cellulose fibers per specified area in any 10 cross sections of the thermoplastic resin composite is 15% or less (however, this does not include a thermoplastic resin composite containing 2 to 20 mass% of a water-soluble resin, and a thermoplastic resin composite containing surface-treated cellulose fibers obtained by mixing a cellulose raw material, a silicone-based surfactant, and a water-based resin in water to surface-treat the cellulose fibers contained in the cellulose raw material).
2. The thermoplastic resin composite material according to claim 1, characterized in that the cellulose fibers have a fiber bending angle of 0 to 60° between the axial direction (A) of the fiber at one end and the axial direction (B) of the fiber at the other end.
3. The thermoplastic resin composite according to claim 1 or 2, characterized in that the composition ratio by mass of the cellulose fiber and the thermoplastic resin is 60:40 to 20:
80.
4. The thermoplastic resin composite according to any one of claims 1 to 3, characterized in that the thermoplastic resin comprises any one of a polyethylene resin, a polypropylene resin, a polyvinyl chloride resin, a methacrylic resin, a polystyrene resin, an ABS resin, a polycarbonate resin, a polyacetal resin, a polyamide resin, a polysulfone resin, a modified PPO resin, and a polyester resin.
5. A thermoplastic resin composite particle comprising a cellulose fiber and a thermoplastic resin, The average fiber length of the cellulose fibers is 10 to 400 μm, The average fiber diameter of the cellulose fibers is 1 to 50 μm, The content of the cellulose fibers is 20 to 80% by mass, where the sum of the mass of the thermoplastic resin and the mass of the cellulose fibers is 100% by mass. Thermoplastic resin composite particles, characterized in that the cellulose fibers are substantially oriented in the axial direction of the thermoplastic resin composite particles (however, excluding thermoplastic resin composite particles containing 2 to 20 mass % of a water-soluble resin, and thermoplastic resin composite particles containing surface-treated cellulose fibers obtained by mixing a cellulose raw material, a silicone-based surfactant, and a water-based resin in water to surface-treat the cellulose fibers contained in the cellulose raw material).
6. The thermoplastic resin composite particles according to claim 5, characterized in that the melt mass flow rate measured at 230°C under a load of 2.16 kgf is 5 to 30 (g / 10 min).
7. The thermoplastic resin composite particle according to claim 5 or 6, characterized in that the cellulose fiber has a fiber bending angle of 0 to 60° between the axial direction (A) of the fiber at one end and the axial direction (B) of the fiber at the other end.
8. The thermoplastic resin composite particle according to any one of claims 5 to 7, characterized in that the thermoplastic resin comprises any one of polyethylene resin, polypropylene resin, vinyl chloride resin, methacrylic resin, polystyrene resin, ABS resin, polycarbonate resin, polyacetal resin, polyamide resin, polysulfone resin, modified PPO resin, and polyester resin.
9. A molded product obtained by molding the thermoplastic resin composite particles according to any one of claims 5 to 8.
Citation Information
Patent Citations
Method for producing thermoplastic resin composition containing cellulose fiber
JP2007084713A
Resin composition
JP2012236906A
Manufacturing method of fibrillated cellulose fiber, and manufacturing method of resin composition
JP2019001938A
Composition and molded body, and manufacturing method of them
JP2019147861A
Fiber composite resin composition and manufacturing method therefor
JP2019157049A